ASSISTANCE FOR DISASTER NUTRITION INTERVENTION THROUGH FOOD SUPPLY MANAGEMENT ACTIVITIES, NUTRITION COUNSELING AND EDUCATION - Prastia, Tika Noor; Dewi Pertiwi, Fenti; Nasution, Andreanda (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Indonesia's geographical conditions make Indonesia a region prone to disasters, one of which is an earthquake. Cianjur Regency is one of the areas affected by an earthquake at the end of 2022. Disasters also open up opportunities for new disasters to emerge on public health status. Food and nutrition are basic needs that are important to be concerned about and focus on in handling emergencies because they determine health status. The Bangkit Village Activity Program (KKB) aims to find solutions to post-earthquake disaster nutrition management problems. This program is carried out through several activities, namely Rapid Nutritional Survey, Food Supply Management, Counseling, and Nutrition Education. The target of this activity is disaster-affected communities, especially special groups, namely infants, toddlers, pregnant women, breastfeeding, and the elderly. The results of the activities show a positive impact with the availability of data describing the health status of the community, increasing knowledge through education, exploring health problems through counseling, and quality assurance and food safety. The sustainability of the program needs to be considered by all parties involved to improve the health status of disaster-affected communities in Nagrog Village, Cigrass Village, and Cugenang District.